OPTIMALISASI DANTON DURLAP BEKANG AKMIL DALAM MENINGKATKAN KEMAMPUAN PELAYANAN DAPUR LAPANGAN GUNA MENDUKUNG LATIHAN TARUNA - Kuntarti, Rita; Aji Wijayanto, Zanuar; Aji Wijayanto, Budiyanto (JURNAL DWIJA KUSUMA, 2024)
The Supply and transport Corps at the Military Academy has 3 main functions consisting of provision services, services and maintenance of provisions/transport supplies in order to support the main tasks of the Military Academy. The Bekang Akmil Corps as the person responsible for providing transportation at the Military Academy has the task of preparing facilities, infrastructure and field equipment as well as preparing logistics and transportation services which are really needed to ensure the smooth implementation of unit activities at the Military Academy, both organic military and civil servants, as well as for Military Academy Cadets. This research aims to determine the optimization, barriers and constraints of Danton Durlap Bekang Akmil in improving the capability of field kitchen services to support cadet training. The research method used is qualitative research. Data collection using interviews, document study and observation. Subjects/sample research data sources selected by Bekang Akmil personnel who have a correlation with the research. The results of the research show that the field kitchen services of the Bekang Akmil Service Unit consist of services for Widya Yudha training, Yudha Scouts, Latsitarda, and Cadet training where it is not possible to return to home base just to eat. Apart from that, several obstacles were found, such as the limited ability of the field kitchen to serve, the lack of effective and efficient time, and the hygienic level of the equipment was still lacking. As an effort to use the latest field kitchens and increase the number of service personnel and increase the professionalism of personnel in the field of management by providing opportunities for further education.